Fragile frontiers: the secret history of Mumbai terror attacks - Saroj Kumar Rath
Using new insights, it explores South Asia's regional dynamics of antagonism, the ever-present challenge to the frontiers of India, Pakistan and the terrorism question, the strife in Afghanistan and the self-serving selective US 'war on terror'. Critical questions remain unanswered on the events of the cold-blooded and devastating terror in Mumbai on 26 November 2008.
Keywords: Mumbai Terrorist Attacks; Terror Attack; Terrorism India; Social Sciences